REVIEWING THE TRACES OF ISLAMIC CIVILIZATION IN THE OLD BANTEN REGION: MENINJAU KEMBALI JEJAK PERADABAN ISLAM DI KAWASAN BANTEN LAMA - Leihitu, Irsyad (The Department of Islamic History and Culture in cooperation with the Center for Islamic History and Culture in Aceh and Malay World Studies (PUSAKA), Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia, 2023)
The Old Banten region is proof of the greatness of the Banten Sultanate, which once stood in the west of Java Island for nearly three centuries. Many experts have studied the historical data, such as the explorer's travel notes or ancient maps, and done a lot of excavation to discover evidence that describes the splendor of the Banten Sultanate civilization. Even so, several archaeological data around the area are still untouched and can be explored. Based on the studies conducted, by combining the latest research, historical sources, and field observation data, the results show a match between the historical data and the current archaeological evidence. This paper also explores the areas considered as potential for future research.